Possibilities of transformation: Women's Studies in Tier II cities in Tamil Nadu, India. Issue 5 (3rd September 2018) - Kanagasabai, Nithila
ABSTRACT: Existing scholarship on knowledge mobilities tends to focus on the largest metropolitan centres as loci of education and employment and as desirable destinations for knowledge migrants. This paper draws attention to the ways in which the spaces of learning in non-metropolitan locations intersect with circulations of disciplinary knowledge and aspiration to generate opportunities for social and spatial mobility. It is premised on the idea that the experiences and situated knowledge of those engaged in women's studies in Tier II cities are apposite starting points for a critical reflection on non-metropolitan locations as brokers of student mobilities. Focusing on two government-funded Women's Studies Centres in universities in the state of Tamil Nadu, India, I explore the transformations catalysed by these mobilities and discuss the politics of the personal – by rethinking the notions of home and alienation, and reflecting on the re-imagination of futures that Women's Studies (WS) has permitted.